2011
DOI: 10.1007/s00213-011-2423-0
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong CRF overproduction is associated with altered gene expression and sensitivity of discrete GABAA and mGlu receptor subtypes

Abstract: RationaleRepeated activation of corticotropin-releasing factor (CRF) receptors is associated with increased anxiety and enhanced stress responsivity, which may be mediated via limbic GABAergic and glutamatergic transmission.ObjectiveThe present study investigated molecular and functional alterations in GABAA receptor (GABAAR) and metabotropic glutamate receptor (mGluR) responsivity in transgenic mice that chronically overexpress CRF.MethodsCRF1 receptor, GABAAR, and mGluR sensitivity were determined in CRF-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Within the BLA, it appears that the CRF system and GABAergic systems modulate each other. CRF overexpression leads to changes in GABA receptor subtype expression and sensitivity (Vinkers et al, ). GABAergic disinhibition or CRF excitation both result in increased excitability of neurons within the amygdala (Sajdyk, Schober, Gehlert, & Shekhar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the BLA, it appears that the CRF system and GABAergic systems modulate each other. CRF overexpression leads to changes in GABA receptor subtype expression and sensitivity (Vinkers et al, ). GABAergic disinhibition or CRF excitation both result in increased excitability of neurons within the amygdala (Sajdyk, Schober, Gehlert, & Shekhar, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent article investigated the effects on GABA and glutamatergic transmission in CRH-OE 2122 [ 74 ]. The study showed that constitutive overexpression of CRH reduced sensitivity to the anxiolytic effects of CRH-R1 antagonists, and GABA A and glutamate receptor agonists in response to stress-induced hypothermia.…”
Section: Genetically Altered Rodent Modelsmentioning
confidence: 99%
“…The study showed that constitutive overexpression of CRH reduced sensitivity to the anxiolytic effects of CRH-R1 antagonists, and GABA A and glutamate receptor agonists in response to stress-induced hypothermia. Additionally, mRNA levels of distinct subunits of the GABA A receptors and mGluR 2/3 receptor were differentially altered in amygdala versus the hypothalamus [ 74 ]. The data supports the notion that an imbalance in GABAergic and glutamatergic transmission may underlie the genesis of stress-related maladaptive behaviors.…”
Section: Genetically Altered Rodent Modelsmentioning
confidence: 99%
“…CRF administration increases GABA release within the amygdala (7,8) and causes deficits in GABA(A) receptor-mediated inhibitory transmission (9). Lifelong CRF overexpression leads to changes in GABA receptor subtype expression and sensitivity (10). Furthermore, GABAergic disinhibition or CRF excitation leads to long-term synaptic plasticity and increased excitability of neurons within the amygdala (11,12).…”
mentioning
confidence: 99%